DETERMINANTS OF SUSTAINABILITY REPORTING QUALITY: EMPIRICAL EVIDENCE ON GREEN ACCOUNTING, DIGITAL INNOVATION, AND CYBER GOVERNANCE - Lisna Lisnawati; Erfan Erfiansyah ((JRAMB) Jurnal Riset Akuntansi Mercu Buana, 2026)
Sustainability reporting is at a mature stage for implementation, both in practice and as a standard in Indonesia. However, there are gaps in the quality of sustainability reports across many sectors, including the industrial sector. The purpose of this study is to examine factors that may influence the quality of sustainability report presentation. The method used is quantitative with secondary data testing using PLS-SEM. Data were collected using content analysis of SR/FR/AR in the industrial sector in 2024. Using a purposive sampling technique, a sample of 100 companies in the industrial sector was determined. The results show that green accounting and digital innovation have an impact on the quality of sustainability reports, while cyber governance does not. Cyber governance has no effect because its primary focus is on risk management and information system security, rather than on the completeness of sustainability disclosures. This study provides practical implications for companies to improve the quality of sustainability reports through the implementation of green accounting and digital innovation. This study also adds to the empirical research related to the quality of sustainability reports.